Flipping the Script in Study Abroad Participation: The Influence of Popular Culture and Social Networks - Nguyen, Shelbee; Coryell, Joellen E. (Journal of International Students, 2015)
This study explores primary perceptions of and motivations to study abroad for adult and higher education learners. A large Hispanic-serving Southwestern university serves as the context of this study where undergraduate students and one graduate student were enrolled in an Italian urbanism study abroad program. The age of the participants ranged from 20 to 47, with six males and 11 females (N = 17) for an average age of 25. Participants self-identified as Caucasian (35%), Asian (6%), Latino/a (24%), Middle-Eastern (6%), and Mexican-American (52) %. Semi-structured interviews assessed formative and influential messages impacting perceptions of and motivations to study abroad. Findings lend special importance to popular culture, peer networks within and outside the institution and socially constructed meaning made about study abroad. Limitations of this study are highlighted, along with implications and directions for future research.